Exploring the constraints regarding maternal health in reproductive age among the rural women in Bangladesh (Mediscope, 2016)
The study evaluated the constraints of maternal health in reproductive age in the rural Bangladesh. The study used qualitative approach to gather information where individual in-depth interviews adopted for data collection among women aged 15-49 years old. The overall study revealed that rural women faced many maternal health related complications and problems in their reproductive age such as hemorrhage, sepsis, hypertensive diseases of pregnancy, obstructed labour and complications of abortion, etc. Maternal health situation still in rural areas was not developed in comparison to the situation of urban areas of Bangladesh and there was not available womens health care accesses for their emergency; low education level, low per capita income, many family members, early marriage and pregnancy, number of pregnancies, poor nutrition and lack of family support status resulted in low status of maternal and child health in the rural areas of Bangladesh. Adequate measures should be taken for providing proper health care services in rural areas of Bangladesh for better maternal health status.Mediscope Vol. 3, No. 2: July 2016, Pages 1-10